Multilevel and multisite leadership development from a leadership-as-practice perspective: an integrative literature review - Lehtonen Salla; Seeck Hannele (Emerald, 2022)
Purpose
This paper reviews what has been written on leadership development from the leadership-as-practice (L-A-P) perspective, which views leadership as emerging in everyday activities and interactions of a collective in a specific context. This paper aims to deepen the theoretical understanding of how leadership can be learned and developed from the L-A-P perspective.
Design/methodology/approach
An integrative literature review was undertaken to review and synthesise what has been written on the topic in journal articles and scholarly books.
Findings
The importance of the context and the practices that are embedded in it is the most central aspect affecting leadership development from the L-A-P perspective. This places workplace leadership development centre stage, but several papers also showed that leadership programmes have an important role. Not only collective capacity building is emphasised in the papers, but the importance of individual-level leader development is also recognised.
Originality/value
The contribution of this study is twofold: First, it brings the currently fractured information on L-A-P development together to enhance theory building by providing a synthesis of the literature. Second, a conceptual framework is constructed to show how the L-A-P perspective on leadership development can take both leadership development at the collective and individual levels into account, as well as the learning that takes place either inside or outside the workplace. This study's results and framework show that the development has its own specific purpose and suggested methods in both levels, in both learning sites.